Reflective and critical thinking in nursing curriculum - María Antonia Jiménez-Gómez; Lucila Cárdenas-Becerril; Margarita Betzabé Velásquez-Oyola; Marcela Carrillo-Pineda; Leyvi Yamile Barón-Díaz (Universidade de São Paulo, 2019)
Objective: to evaluate the teaching of transversal competence of the Reflective and Critical Thinking that is fundamental in the decision-making and solution of nursing problems, in degree programs of public and private institutions in the Andean region. Method: multi-center, cross-sectional, exploratory-descriptive study, with mixed approach in 5 countries. Results: 76 nursing programs participated in the study. The Reflective and Critical Thinking was found as a subject, subject content and didactic strategies. Of the 562 subjects reviewed, this type of thinking is found in 46% of the humanities area and 42% in the area of research and professional discipline. It is important to train teachers to achieve coherence between the pedagogical model approach, teaching strategies and evaluations. Conclusion: nursing programs in the Andean region contemplate the critical thinking as cognitive and personals skills of communication. They also use real situations analysis, supervised practice, simulation labs and specifically learning based in problems to develop the capacity to solve them, decision-making and develop communication skills, including analysis, synthesis and evaluation.